Quantitative Measurements of Breast Density Using Magnetic Resonance Imaging - Sindi, Rooa (Curtin University, 2021)
This study was conducted to investigate the optimal MRI protocols for quantitative assessment of breast density. The research involved development of a patient-specific 3D-printed breast phantom for simulation of breast tissues and quantitative analysis of breast density based on phantom experiments and patient data analysis. Results of this research highlight the importance of standardising breast MRI protocols for the evaluation of breast density, predominantly for women at an elevated risk of developing breast cancer.